Maria Petyt - Chalmers, J. (Radboud Studies in Humanities, 2015)
Based on the discovery of an unknown Latin manuscript, Maria Petyt - A Carmelite Mystic in Wartime provides surprising new information about the seventeenth century Flemish mystic Maria Petyt (1623-1677) who wrote many letters to her spiritual director, Michael of St. Augustine.